2011
DOI: 10.1590/s1516-35982011000700006
|View full text |Cite
|
Sign up to set email alerts
|

Área foliar específica e anatomia foliar quantitativa do capim-braquiária e do amendoim-forrageiro submetidos a sombreamento

Abstract: RESUMO -A área foliar específica e as características anatômicas foliares da braquiária (Brachiaria decumbens cv.Basilisk) e do amendoim-forrageiro (Arachis pintoi cv. Amarillo) foram avaliadas em resposta a níveis de sombreamento artificial (0, 50 e 70%), com o objetivo de se determinar a aclimatação destas forrageiras às modificações no ambiente luminoso.Utilizou-se o delineamento em blocos completamente casualizados, com três repetições. Foram realizados três e dois cortes, respectivamente, para avaliação d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
2
30

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 19 publications
(18 reference statements)
4
40
2
30
Order By: Relevance
“…Under lower irradiation grasses accelerate the growth of their photosynthetic apparatus. This pattern was also reported by Gobbi et al (2011), who found a significant increase in the leaf blade of Urochloa decumbens cv. Basilisk, grown in shaded areas.…”
Section: Resultssupporting
confidence: 87%
“…Under lower irradiation grasses accelerate the growth of their photosynthetic apparatus. This pattern was also reported by Gobbi et al (2011), who found a significant increase in the leaf blade of Urochloa decumbens cv. Basilisk, grown in shaded areas.…”
Section: Resultssupporting
confidence: 87%
“…In both the dry and rainy periods, the CP content was higher in the silvopastoral system (Tables 1 and 2). This response is common in shaded pastures and is well described in the literature (Paciullo et al, 2007;Gobbi et al, 2011). According to Xavier et al (2014), shade conditions lead to an increase of organic matter degradation and soil-nitrogen recycling, which favors an increase of protein level.…”
Section: Resultsmentioning
confidence: 70%
“…The lower content of DM in the silvopastoral system is probably associated with the higher-moisture content in the plants under shade, as a result of the milder microclimate around the trees, which reduces the evapotranspiration and keeps the plant more tender and succulent for longer (Sousa et al, 2007). The elevation of NDF content in the pasture under full sun may be associated with the higher proportion of sclerenchymatous tissue (Gobbi et al, 2011). Cells exhibit walls that are thicker under conditions of high luminosity than under shading conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Diferenças de AFE e, consequentemente, de espessura de folhas, são, frequentemente, observadas quando as plantas são submetidas a sombreamento (Garcez Neto et al 2010, Gobbi et al 2011. Segundo (Gobbi et al 2011), o aumento da AFE, em folhas de Urochloa decumbens cv.…”
Section: Methodsunclassified
“…Segundo (Gobbi et al 2011), o aumento da AFE, em folhas de Urochloa decumbens cv. Basilisk, foi acompanhado pela redução linear da espessura da folha, em função de níveis crescentes de sombra.…”
Section: Methodsunclassified